Many Labs 5: Registered Replication of Förster, Liberman, and Kuschel's (2008) Study 1. Issue 3 (September 2020) - IJzerman, Hans; Ropovik, Ivan; Ebersole, Charles R.; Tidwell, Natasha D.; Markiewicz, Łukasz; de Lima, Tiago Jessé Souza; Wolf, Daniel; Novak, Sarah A.; Collins, W. Matthew; Menon, Madhavi; de Souza, Luana Elayne Cunha; Sawicki, Przemysław; et al.
In a test of their global-/local-processing-style model, Förster, Liberman, and Kuschel (2008) found that people assimilate a primed concept (e.g., "aggressive") into their social judgments after a global prime (e.g., they rate a person as being more aggressive than do people in a no-prime condition) but contrast their judgment away from the primed concept after a local prime (e.g., they rate the person as being less aggressive than do people in a no prime-condition). This effect was not replicated by Reinhard (2015) in the Reproducibility Project: Psychology. However, the authors of the original study noted that the replication could not provide a test of the moderation effect because priming did not occur. They suggested that the primes might have been insufficiently applicable and the scenarios insufficiently ambiguous to produce priming. In the current replication project, we used both Reinhard's protocol and a revised protocol that was designed to increase the likelihood of priming, to test the original authors' suggested explanation for why Reinhard did not observe the moderation effect. Teams from nine universities contributed to this project. We first conducted a pilot study ( N = 530) and successfully selected ambiguous scenarios for each site. We then pilot-tested the aggression prime at five different sites ( N = 363) and found that it did not successfully produce priming. In agreement with the first author of the original report, we replaced the prime with a task that successfully primed aggression (hostility) in a pilot study by McCarthy et al. (2018). In the final replication study ( N = 1, 460), we did not find moderation by protocol type, and judgment patterns in both protocols were inconsistent with the effects observed in the original study. We discuss these findings and possible explanations.